Anemia, Thrombocytopenia, and Changes in Biochemical Parameters Occurring in Patients with Uncomplicated Plasmodium falciparum Malaria: Data Analysis from Antimalarial Efficacy-Randomized Trials in Dakar and Kaolack Regions, Senegal. (22nd December 2022) - Sylla, Khadime; Tine, Roger; Sow, Doudou; Lelo, Souleye; Abiola, Annie; NDiaye, Jean Louis; NDiaye, Magatte; Folly, Kuaku; NDiaye, Léon Amath; Gaye, Oumar; Faye, Babacar
Abstract : Background . Artemisinin-based Combination Therapies (ACTs) are widely used in the treatment of uncomplicated malaria. Plasmodium falciparum infection is often accompanied by disturbances of hematological and biochemical parameters. The objective of this study was to evaluate the changes in biochemical and hematological parameters during uncomplicated malaria in patients treated with ACTs. Methods . Data from patient with uncomplicated Plasmodium falciparum malaria were pooled from different open-randomized trial evaluating the efficacy of Artesunate-Mefloquine (ASMQ), Artesunate-Amodiaquine (ASAQ), Artemether-Lumefantrine (AL), and Dihydro-artemisinin-Piperaquine (DHAPQ) combinations. Biochemical (transaminases, creatinine, and bilirubin) and hematological (hemoglobin and platelet levels) parameters were performed at baseline (D0) and at day 7 after treatment (D7). Data were analyzed as both continuous and categorical variables with 95% confidence interval. Risks and trends were calculated using multivariate logistic random effect models. Results . A total of 720 patients with completed biological data were included in the analysis (320 in the AL arm, 160 in the ASMQ arm, 120 in the DHAPQ arm, and 88 in the ASAQ arm). The mean age of the patients was 9.43 ± 9.1 years. Male subjects represented 58.47% (sex ratio was 1.4 for males). The mean hemoglobin level at inclusion (D0) was 9.79 g/dl and anemia (Hb < 11   g / dl ) was 71.43% (aOR = 1.16   0.68 − 1.98 p = 0.57 ). At D7, hemoglobin level was 9.63 g/dl and anemia was significantly more frequent (78.29% [p = 0.002 ]). The mean platelet count at day 0 was 154075.5 platelets/mm 3 of blood and 339328.7 platelets/mm 3 at day 7. Thrombocytopenia was about 53.61% and was associated with malaria (aOR = 3.4   2.18 − 5.3 p < 10 − 3 ). 19.58% of patients had abnormal ALT and 40.28% had abnormal AST at D0. 27.22% of patients had normal bilirubin at D0. Renal function was normal in all patients in the study. Normalization of transaminases was noted between D0 and D7. The percentage of subjects with normal bilirubin increased between D0 and D7. Renal function did not vary significantly between D0 and D7. Conclusion . Results from this analysis showed that subjects with high parasitaemia had a greater risk of anemia and thrombocytopenia. Artemisinin combinations were well-tolerated as no major biological disturbances were noted. The effects of ACTs on hematologic and biochemical parameters were not different.